Ketentuan Kompilasi Hukum Islam tentang Kekuasaan Orang Tua Memaksa Kawin Anak Usia 21 Tahun - Muhammad Ihwan (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2023)
The occurrence of a marriage based on the consent of the child is a marriage requirement by the compilation of Islamic law article 16 paragraphs 1 and 2 that marriage is based on the consent of the prospective bride and groom, and the form of consent of the prospective bride can be in the form of a firm and real statement in writing, verbally, or with gestures and also by acting. silence as a sign of no objection to the marriage process. As explained in article 98 paragraph 1 of the compilation of Islamic law, "the age limit for a child who can stand alone or be an adult is 21 years", as long as the child is not physically or mentally disabled or has never been married. Library research is a study that studies various reference books and the results of similar previous research which is useful for obtaining a theoretical basis regarding the problem being studied. Based on a review of the literature, it can be explained that parents forcing their children aged 21 years to marry is not permissible based on Article 98 paragraph 1 of the compilation of Islamic law, but it is permissible for children under 21 years of age. In this research, it can be recommended that several factors are behind parents often forcing their children into marriage, namely, local traditions, the desire of parents in the form of responsibility, and on the basis of an antipathetic understanding of one of the concepts of the Imam Madzhab.